Pengaruh Iklan Sosial Media, Influencer Marketing, dan Electronic Word-of-Mouth terhadap Keputusan Pembelian Produk Kecantikan Avoskin (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Tsania Mutamassikah Biddin Nasir; Achmad Agus Priyono; Sulton Sholehuddin (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The rapid development of industry and technology, as well as the emergence of various creative and innovative technology-based business ideas. Avoskin Beauty is one of the creative and innovative business ideas in the field of beauty and care. This study aims to analyze the influence of social media advertising, influencer marketing, and electronic word-of-mouth (e-WOM) on purchasing decisions for Avoskin beauty products. This research is a quantitative research. The sampling technique uses the methodpurposive sampling, from active students of Class 2019 and 2020 in the Management Study Program, Faculty of Economics and Business, UNISMA users of Avoskin Beauty who are 17 years and over. The number of samples was determined by the Malhotra formula so that 80 respondents were obtained. The results of the study show that partially social media advertising,influencer marketing, andelectronic word-of-mouth (e-WOM), positive and significant effect on purchasing decisions of Avoskin beauty products. Simultaneous social media advertising, influencer marketing, and electronic word-of-mouth (e-WOM) has a significant positive effect on the decision to purchase Avoskin beauty products. Keywords: Social Media Advertising, Influencer Marketing, Electronic Word-Of-Mouth (e-WOM), Purchase Decisions.